Penerapan Activity Based Costing Sebagai Alat Bantu Pengendalian Biaya dan Efisiensi Layanan pada PT Yofanka Bersama Utama - Pangau, Clearry Julistya; Saerang, David Paul Elia; Pusung, Rudy J. (Manajemen Bisnis dan Keuangan Korporat, 2025)
Accurate cost control is an important element for service companies, including PT. Yofanka Bersama Utama (YBU), which operates in the field of WiFi installation. In facing increasingly tight industrial competition, companies need methods that are able to provide transparent and accurate cost information to ensure operational efficiency and support strategic decision making. This research aims to determine the application of the Activity Based Costing (ABC) method which can be used as an effective cost control tool in various operational activities at PT. Yofanka Bersama Utama. The object of this research is PT. Yofanka Bersama Utama, with a focus on operational activities that support company cost control. The method used in this research is descriptive qualitative with data collection techniques in the form of in-depth interviews with parties who are directly related to company operations. The research results show that the ABC method helps PT. Yofanka Bersama Utama in controlling operational costs and increasing service efficiency more effectively and transparently. This can be seen from controlling costs in various activities such as material preparation, WiFi installation, device maintenance, and providing other supporting resources. With the ABC method, companies can identify in detail the allocation of costs for each operational activity, reduce waste and increase cost accuracy.